Pengaruh Human Capital Management dan Structural Capital terhadap Profitabilitas, dan Dampaknya terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan StartUp) - Nuraeni, Nuraeni; Hakim, Luqman; Nurdin, M. Arief Firman; Hasan, Diana; Kinasih, Dini Hadiati Putri (Dinasti Review, 2023)
This research analyzes the influence of human capital management and structural capital on company profitability, and its impact on company value. The research objects are startup companies listed on the IDX in 2019-2022. The test used is path analysis which is processed using Eviews.